Mimpi yang Berdampak: Sebuah Pengantar - Mieke Manu (Ra'ah: Journal of Sociology of Religion, 2024)
This research is a preliminary study to evaluate and assess the impact of dream experiences on the community of Kupang city. The approach employed was quantitative with a survey method. The data collecting technique was closed questionnaires disseminated online. The respondents selected by simple random sampling in this online poll comprised 107 persons. The technique utilized to test the research data was univariate analysis with the assistance of SPSS for Windows version 25.0. The calculation results show a mean value of 42.96 and a standard deviation of 8.803. This data was analyzed based on the assessment guideline criteria, establishing that dreams have a high to very high impact, with 61.7% of respondents rating dreams as having a major to very significant impact on their lives. Thus, this work has to be examined further both conceptually and empirically with additional in-depth follow-up studies to investigate the significance of impactful dreams encountered by the research sample. This study serves as a core reference for investigating the subject of significant dreams, particularly from the perspective of Christian theology, which is rarely studied.